Reversal theory-based sport and exercise research: A systematic/narrative review. (November 2016) - Hudson, Joanne; Males, Jonathan R.; Kerr, John H.
Abstract: Objectives: To provide a critical combined systematic/narrative review of reversal theory (RT) sport and exercise research published over the last 30 years. Design: Peer-reviewed journal publications on reversal theory sport and exercise research from 1985 to 2014 were critically scrutinized. Method: Research results were examined using four important research themes: (1) evidence that all motivational states have been reported and provide a valid description of athletes' experience; (2) evidence supporting the reversal process and its causal factors; (3) the role of motivational dominance and participation in different types of sport and exercise; (4) the relationship between motivational state and performance. Results: The richness of competitors' emotional and motivational experience in sport can be mapped and described using RT. Motivational reversals do occur for the reasons suggested by RT, and provide a mechanism for understanding, predicting and influencing changes in affective state. There is a relationship between motivational dominance and participation and experience of different sports. The relationship between particular motivational states and performance was found to be ambiguous. Conclusions: This review has shown that, despite limitations and some gaps in the research literature, past RT sport and exercise research has provided important information and a reason for cautious optimism about its applicability to sport and exercise. However, there is a need for additional robust research. For example, there is evidence supporting the causal factors for reversals, but currently no research has shown that reversals can be controlled, or that motivational states can be reliably induced at will in the context of sport and exercise.